Feasibility Analysis of Shallot Farming in Cimaung District, Bandung Regency (Case Study of Female Farming Customers of Bank BTPN Syariah) - Amalia Diandra; Sri Maryati; Pande Komang Suparyana (Agriwar Journal, 2024)
This research aims to analyze the feasibility and determine the obstacles faced by Women Farming Customers of Bank BTPN Syariah in carrying out shallot farming in the Cimaung District. This research was conducted in Sukamaju Village which was determined using purposive sampling. Respondents were determined using "purposive sampling" with a total of 3 BTPN Syariah Bank customers who received sharia financing. The analytical tools used in this research are descriptive analysis, cost and income analysis, and feasibility analysis (R/C and BEP). The results of the research show that the red onion farming of Bank BTPN Syariah customers in Cimaung District, Bandung Regency is suitable for cultivation based on the R/C ratio value of 2.51 which is greater than 1. Feasibility can also be seen from the BEP for production of 1,454 kg, which is smaller than the production of 2,667 kg, the price BEP of IDR 9,590/kg is smaller than the product selling price of IDR 16,875/kg, and the Revenue BEP of IDR 11,378,664 is smaller than the revenue of IDR 45,000,000. Obstacles to the red onion farming of Bank BTPN Syariah customers in Cimaung District, Bandung Regency include technical obstacles in the form of pest and disease attacks, as well as unpredictable weather. Meanwhile, the economic obstacles faced by Women Farmers are fluctuations in selling prices which can affect the income that Women Farmers will earn. Women Farmers, customers of Bank BTPN Syariah, are expected to pay attention to the weather at planting time to increase shallot productivity. And be more proactive in looking for information related to market information, especially product selling prices so as not to experience losses.